Impact of national and supranational policies on social inequalities in major NCDs and related risk factors in Europe: a scoping review protocol - Mall Leinsalu; Rainer Reile; Norun Hjertager Krog; Digo Chakraverty; Gerd Monika Flodgren; Julia Doetsch; Trude Robsahm; Astri Syse; Kadri Tammur; Julia Waldhauer (BMJ Open)
Introduction There is evidence for significant inequalities in morbidity and mortality due to cancer and other major non-communicable diseases (NCDs) both within and between European countries. Up-to-date evidence highlighting best practices for future policies is needed to reduce these inequalities.Methods and analysis The objective is to map and summarise published evidence on the impact of national and/or supranational policies on social inequalities in cancer and other NCDs, and their risk factors in Europe, and explore the nature and characteristics of these policies. The criteria for studies to be included are Population: any population group(s), whole population(s) or supranational population in Europe. Concept: any national or supranational policy directly targeting social inequalities in NCDs and/or their risk factors, or NCDs or their risk factors in general, while reporting effects on inequalities or targeting root causes of social inequality. Context: policies implemented by one or more governments or authorities in the WHO European region, in one or more sectors, and applied in a primordial, primary, secondary or tertiary prevention context. The policies may be universal, targeted or proportionate universal. The review will follow the Johanna Briggs Institute guidelines and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for scoping reviews. We will search 13 databases from 2008 up to present for eligible experimental or quasi-experimental studies in any language, and reference lists of relevant reviews and included studies. The databases for the main search will include MEDLINE, Embase, Cochrane CENTRAL, Global Health, American Psychological Association (APA) PsycInfo, Cumulated Index in Nursing and Allied Health Literature (CINAHL), Education Resources Information Center (ERIC), Web of Science Core Collection, Sociological Abstracts, Scopus, EconLit, The Social Interventions Research and Evaluation Network and FRANCIS. Study quality will be assessed using the Effective Practice and Organisation of Care (EPOC) risk of bias tool or the Risk of Bias in Non-Randomised studies of Interventions (ROBINS-I) tool depending on study design. Results will be synthesised narratively using descriptive statistics and visuals.Ethics and dissemination Ethical approval will not be sought as scoping reviews do not involve primary data collection or direct interaction with human participants. The results of this review, which is part of the JA-PreventNCD project, funded by the European Commission, and involving 25 European countries, will feed into one of the project’s deliverables, which comprises recommendations for policymakers based on the best available knowledge. We will also aim to present the results of the review at international conferences and publish the full review in an international peer-reviewed journal.Registration This protocol is registered on Open Science Framework (https://doi.org/10.17605/OSF.IO/H7MUW).